2010
DOI: 10.1007/s10695-009-9335-5
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K-dependent γ-glutamylcarboxylase in Atlantic salmon (Salmo salar L.)

Abstract: Due to problems with bone deformities in farmed Atlantic salmon, there is a growing interest in the possible involvement of vitamin K in normal bone development, and sensitive biomarkers for evaluating vitamin K status are therefore needed. The vitamin K-dependent (VKD) enzyme gamma-glutamylcarboxylase (GGCX, EC 6.4.x.x) requires vitamin K as a cofactor for its post-translational modification of glutamic acid (Glu) residues to gamma-carboxyglutamic acid (Gla) residues in VKD proteins, and is required for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Menadione must be alkylated enzymatically to MK‐4 in animal tissues to become biologically active (Udagawa 2000), and is thought to have lower bioavailability than the naturally occurring K vitamers, as shown in mummichog (Udagawa 2001; Udagawa & Murai 2001). Results from Krossøy et al. (2010) confirmed that menadione did not act directly as a co‐factor for GGCX in Atlantic salmon, despite its structural similarities with the inherent vitamin K forms (Lambert & De Leenher 1992).…”
Section: Menadione As a Vitamin K Source In Fish Feedmentioning
confidence: 82%
See 2 more Smart Citations
“…Menadione must be alkylated enzymatically to MK‐4 in animal tissues to become biologically active (Udagawa 2000), and is thought to have lower bioavailability than the naturally occurring K vitamers, as shown in mummichog (Udagawa 2001; Udagawa & Murai 2001). Results from Krossøy et al. (2010) confirmed that menadione did not act directly as a co‐factor for GGCX in Atlantic salmon, despite its structural similarities with the inherent vitamin K forms (Lambert & De Leenher 1992).…”
Section: Menadione As a Vitamin K Source In Fish Feedmentioning
confidence: 82%
“…As the major function of vitamin K is to act as co‐factor for GGCX, the activity of this enzyme may provide a biomarker for deficiency. Results from recent studies in juvenile Atlantic salmon confirmed that GGCX activity is a sensitive marker for evaluating vitamin K status and intake (Krossøy et al. 2009a, 2010).…”
Section: Requirement and Toxicity Of Vitamin Kmentioning
confidence: 91%
See 1 more Smart Citation
“…Menadione is very unstable during feed processing (Krossøy et al, 2009), and the analysed dietary levels of K3 were only 1/10 of the supplemented levels. Menadione is metabolised to menakinones (MK4-13, vitamin K2) in the body (Krossøy et al, 2011) and therefore, MK4 increased in response to increase in dietary vitamin K3, while whole body vitamin K1 was similar in fish fed the different treatments. Krossøy et al (2009) fed Atlantic salmon eight diets supplemented with 0 to 50 mg kg -1 vitamin K3 and found no effects on fish performance, or blood coagulation time and vertebrae stiffness.…”
Section: Lipid Soluble Vitaminsmentioning
confidence: 99%
“…Many of the micronutrients act as important cofactors in enzymatic pathways and other metabolic processes in vertebral formation. Several studies in diploid salmon have demonstrated a key role of nutrients, particularly P and Ca (Åsgård and Shearer, 1997;Baeverfjord et al, 1998), vitamin A (Green et al, 2016) and vitamin K (Krossøy et al, 2010), in skeletal development and either their deficiency or toxicity leads to pathogenesis of skeletal deformities. Vitamin A regulates skeletogenesis and cartilage development by controlling chondrocyte function, maturation and proliferation of cells (Koyama et al, 1999), while vitamin K…”
Section: Introductionmentioning
confidence: 99%